Grain-size effect on coercivity of Nd–Fe–B nanomagnets: micromagnetics simulation based on a multi-grain model. (27th July 2021) - Bao, Lingbo; Yun, Guohong; Bai, Narsu; Cao, Yongjun
Abstract: The coercivity ( H c ) of nanocrystalline Nd–Fe–B magnet was simulated by multi-grain models in combination with hybrid Monte Carlo method. The simulated grain size dependence of H c with grain boundary (GB) model reproduces the available experiment nicely. The H c of direct contact (DC) model increase with the decreasing grain size ( S G ). This fact suggests that the H c of Nd–Fe–B magnets can be further increased by grain refinement even though the average S G down to several tens of nanometers. The difference of coercivity mechanism between GB-model and DC-model was understood by magnetization reversal analysis.